Association between contrast-induced nephropathy and CHA2DS2-VASc score in patient with non-ST elevation myocardial infarction after percutaneous coronary intervention - Siddike, Sohel; Mamunur Rashid, M.; Karmakar, Pradip Kumar; Hamid, M. Abdul; Islam, AFM Rezaul; Das, Saurav; Rahman, Atikur; Hoque, Mohammad Faridul; Aktar, Shameem; Hossan, M. Sawkat (International Journal of Research in Medical Sciences, 2024)
Background: Contrast-induced nephropathy (CIN) is a recognized complication in patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). CHA2DS2-VASc score, commonly employed in clinical settings, shares similar risk factors for CIN development. This cross-sectional observational study investigated the association between CHA2DS2-VASc score and CIN post-PCI in non-ST segment elevated myocardial infarction (NSTEMI) patients. Methods: Over one year (April 2019 to March 2020), 100 NSTEMI patients undergoing PCI at the national institute of cardiovascular diseases (NICVD), Dhaka, were included. Patients were categorized into two groups based on CHA2DS2-VASc scores (≥4, group I; <4, group II). CIN assessment utilized post-procedural serum creatinine within 48 hours, with statistical analysis performed using SPSS version 20.0. Results: Group I exhibited a significantly higher CHA2DS2-VASc score (4.15±1.35 vs. 2.25±0.92 in group II). Post-procedural serum creatinine was notably elevated in CHA2DS2-VASc score ≥4 (1.98±0.46 vs. 1.46±0.27, p<0.001). A CHA2DS2-VASc score cut-off ≥4 predicted CIN with 84.6% sensitivity, 55.2% specificity (AUC 0.83, CI: 0.743-0.90, p<0.001). Conclusions: This study establishes a significant association between CHA2DS2-VASc score and CIN in NSTEMI patients post-PCI, suggesting its potential utility in predicting CIN risk in this population.